EVALUASI PENERAPAN KURIKULUM MERDEKA DALAM MENINGKATAN KREATIVITAS BELAJAR SISWA SMP DAN SMA SE-KECAMATAN BELO - SOADIKINI, AHMAD; ROHMADI, SYAMSUL HUDA; HAIRUDDIN, HAIRUDDIN; PUTRI, TRISKA DEVI SARTONO (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2023)
The Independent Curriculum, designed by the government as a measure for educational recovery, faces challenges in its implementation across various schools. This study aims to assess the effectiveness of the Independent Curriculum in enhancing learning creativity among students in junior and senior high schools within the Belo sub-district. Employing a qualitative descriptive approach, the research utilizes triangulation in data collection through observation, semi-structured interviews, and documentation. Findings indicate that schools encounter multiple obstacles related to teacher competencies, infrastructure, supporting resources, and student engagement. Consequently, the intended goal of fostering increased student learning creativity through the Independent Curriculum has not been fully realized. This study represents a novel evaluation of the Independent Curriculum's impact on student creativity, highlighting areas for further research to explore additional influencing factors. It is anticipated that these findings will guide schools in improving supporting facilities and infrastructure to better support the enhancement of student learning creativity. ABSTRAK Pemerintah merancang kurikulum merdeka sebagai pemulihan pembelajaran, tetapi beberapa sekolah belum mampu menerapkannya dengan baik sehingga perlu adanya evaluasi. Penelitian ini bertujuan untuk mengevaluasi penerapan kurikulum merdeka di SMP dan SMA Se-kecamatan Belo. Penelitian menggunakan metode deskriptif kualitatif, dengan teknik pengumpulan data menggunakan triangulasi, observasi, wawancara semi terstruktur, dan dokumentasi. Hasil penelitian menunjukan terdapat kendala yang dihadapi oleh sekolah baik dari komponen guru, sarana prasarana, sumberdaya pendukung dan siswa. Oleh sebab itu tujuan penerapan kurikulum merdeka dalam meningkatkan kreativitas belajar siswa belum mencapai hasil sesuai dengan yang diharapkan. Evaluasi terhadap penerapan Kurikulum merdeka dalam meningkatkan kreativitas belajar siswa SMP dan SMA belum pernah diteliti sebelumnya. Temuan penelitian diharapkan dapat dikembangkan peneliti selanjutnya dengan mengidentifikasi faktor lain yang belum diteliti. Sekolah diharpakan dapat meningkatkan sarana dan prasarana penunjang dalam upaya peningkatan kreativitas belajar siswa.